INTERESTING FACTORS FOR TOURIST SATISFACTION IN DOUBLE-DECKER TOUR BUS - M. Rifki Bakhtiar; Puji Setya Sunarka (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
Research to analyze tourist satisfaction factors is the development of research on customer satisfaction which is designed based on tourist perceptions. Transportation is the basis for tourism because it connects one destination to another. Using a double-decker bus provides an experience for tourists visiting a destination. Analysis of the influence of service quality, facilities, and destination image on tourist satisfaction is the aim of this study. The questionnaires that met the requirements of purposive sampling were 178 respondents. The data were processed by multiple linear regression analysis using SPSS 25. The results showed that all independent variables had a positive effect on tourist satisfaction. The result of the determinant coefficient test (R2) shows that tourist satisfaction can be explained by the independent variable of 71.2 percent, while the other 28.8 percent is explained by other variables.